Liquid-Crystal Nanomaterials Tribology and Applications - Ermakov, Sergey F.; Myshkin, Nikolai K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book discusses the tribological, rheological and optical properties of liquid-crystal nanomaterials as well as lubricant media. It also describes the formation of liquid-crystal materials and the application of cholesteric liquid-crystal compounds in technical friction units and in human and animal joints. Further, it shows the connection between the tribological and other physical properties of liquid-crystal cholesterol compounds and develops a lubricity conceptual model of cholesteric-nematic, liquid-crystalline nanostructures on the basis of physical and energetic interpretations. This general model is valid for all surfaces and friction pairs, including biopolymers, and could lead to applications of cholesteric liquid-crystalline nanomaterials in different friction units and tribosystems as well as in the treatment of joint diseases.
Introduction -- Structure and Properties of Liquid-Crystal Nanomaterials -- Tribology and Lubrication of Solids -- Engineering and Technique of Experimental Tests of Liquid-Crystal Nanomaterials -- Tribological Properties of Liquid-Crystal Nanomaterials -- Practical Application of Liquid-Crystal Nanomaterials in Engineering and Medicine -- Conclusions.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Soft condensed matter; Microtechnology; Microelectromechanical systems; Nanoscience; Coatings; Tribology; Corrosion; Soft and Granular Matter; Microsystems and MEMS; Nanophysics